ANALISIS KEBIJAKAN PEMBERIAN INSENTIF GURU NGAJI PENDIDIKAN AL-QUR’AN (GURU NGAJI) DI KABUPATEN KAUR - Purnawan, Heru (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research was conducted with the aim of describing the policy of providing incentives given to Koran teachers in educating and teaching students/youth and the role of local governments in providing attention to Koran teachers. The research used in this paper is qualitative descriptive research through case studies. This research data is primary data and secondary data. Data collection methods include observation, interviews and documentary methods. Data analysis techniques include data reduction, data presentation, and decision making/validation. The findings of this research are as follows: The Al-Quran Teacher development policy in Kaur Regency has been managed well and accountably, which is reflected in monitoring indicators which include: 1) Procedures and objectives and targets of policy/practice. , 2) resources, 3) characteristics of implementing agencies, 4) communication and implementation activities between related agencies, 5) attitudes or attitudes of trainers, 6) social, economic and political environment.